2015
DOI: 10.14569/ijacsa.2015.061033
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Poor Inhabitant Number Using Least Square and Moving Average Method

Abstract: Abstract-The number of poor inhabitant in South Kalimantan decreased within the last three years compared with the previous years. The numbers of poor inhabitant differs from time to time. This scaled dynamical number has been a problem for the local government to take proper polices to solve this matter. It will then be necessary to predict a potential number of poor inhabitants in the next year as the basis on subsequent policy making. This research will apply both Least Square and Moving Average method as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…The number of observations used is called the order of the series [13]. Previous researches showed that Single Moving Average can be used to forecast time series data [14][15]. In this research Single Moving Average with order 2 or SMA( 2) is used and calculated with formula below.…”
Section: Methodsmentioning
confidence: 99%
“…The number of observations used is called the order of the series [13]. Previous researches showed that Single Moving Average can be used to forecast time series data [14][15]. In this research Single Moving Average with order 2 or SMA( 2) is used and calculated with formula below.…”
Section: Methodsmentioning
confidence: 99%